Responding to muhammadiyah education in the era of neurotechnology: neuroscience and religious moderation perspectives - Jailani (12 Waiheru, 2023)
In the Millennial era, there's been a positive response to the comprehensive diversification of educational partnerships, especially in the realm of multicultural Islamic education, garnering significant attention. Haedar Nashir's scholarly address at the 48th Mukhtamar of Muhammadiyah in UMS Surakarta effectively illustrates the emergence of a uniform educational framework, rich in intricacies, opening up new avenues in Islamic education. This qualitative and descriptive research addresses the ongoing debates surrounding Islamic education in Indonesia by suggesting pertinent Islamic-centered alternative approaches within the contemporary landscape. By utilizing a systematic review methodology and content analysis, this study highlights various facets of life and learning, encompassing methodologies, techniques, information propagation, educational administration, and the role of social media. Despite the primary emphasis and requirements set by Kemdikbud and Kemenag to achieve an enlightened Islamic education, the current state of Islamic education in Indonesia seems stagnant. The proliferation of educational partnerships extends broadly across diverse educational establishments, both formal and Islamic boarding schools. To notably elevate the quality of education, the researchers propose significant alternatives rooted in neuroscience, religious moderation, and knowledge management within Islamic education. The implications and contributions of this study aspire to enhance Islamic education and advance study-based learning in Islam, with the aim of captivating the attention of younger generations, notably millennials and Generation Z, within the realm of Society 5.0. This research is expected to serve as a platform and pivotal milestone in realizing a progressive and flourishing Islamic civilization in the forthcoming times.